Physiological Importance of Pachakpitta in Aaharpaka (Digestion) in Modern Perspective - Sajwan, Neha; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2022)
The tridosha theory drives Ayurveda science. Pitta is one of the three doshas and is responsible for digestion and metabolism. There are five forms of Pittadosha: Pachaka, Ranjaka, Alochaka, Bhrajaka, And Sadhakapitta. Pachakapitta is in charge of food digestion, Sara and Kitta Vibhajan, and nourishing the Agneya component of Pitta in various sections of the body. Jatharagni is another name for it. Pitta’sagni aids digestion and then separates the Sara and Kittabhaga. Because of its location, it nourishes and strengthens Pitta. PachakaPitta is to blame for AaharPachan, as our book clearly demonstrates.On the other hand, current or contemporary science has proven via several research those distinct digestive fluids are responsible for food digestion. All enzymes involved in digestion, such as amylolytic, proteolytic, and lipolytic enzymes, can be compared to pachakapitta, as its activities suggest. Only a few works on pitta’s conceptual elements have been mentioned. The importance of pachakpitta in food digestion is discussed in this article. The core resources for this study were gathered from Ayurvedic classics with available commentaries, as well as modern medical science textbooks to gain a better grasp of the concept and its usefulness in digestion.